(untitled) - José-Luis Álvarez-Galván; OECD (OECD, 2014)
Ebook from OECD
Keywords: Education -- Vocational Training -- Kazakhstan ; Giáo dục -- Đào tạo nghề -- Kazakhstan; Apprenticeship systems -- Kazakhstan